(untitled) (Revista de Estudos da Linguagem, 2024)
On January 2021 Brazil kicked off its nationwide COVID-19 vaccination campaign. Former President Jair Bolsonaro argued that scientists and the media were hyping the seriousness of a virus that took the lives of over 700,000 Brazilians. In this article, we discuss a case study in which different forms of figurative language are employed by a comedian called Marcelo Laham from the group “Embrulha para Viagem” (“Pack to takeaway” in Portuguese). We present some background information about the Brazilian coronavirus crisis at the time the first video was launched in June 2020. Then, we present step by step how the comedian, who personifies COVID-19 as a celebrity, introduces the coronavirus pandemic in the world and its first wave in Brazil by means of figurative verbal and multimodal language. We also present some current facts about the surge of a new coronavirus strain in the northern state of Amazonas, which is home to the Amazon rainforest, considered the ‘lung of the world’, and where a large number of COVID-19 patients asphyxiated to death due to the lack of oxygen tanks in hospitals. These events were described in the first and second videos in terms of an allegory that portrayed COVID-19 as a star on a world tour. The next surge due to a coronavirus mutation is represented by the use of different figurative, also multimodal language, which encompasses metaphor, irony and allegorical expressions. Our analysis demonstrates how productive an allegory can be as a creative means of expressing irony.